A new type of plasma knife and its effect on biological issues--a pilot study - Justan, I; Tichý, F; Slavícek, P (Acta chirurgiae plasticae, 2010)
BACKGROUND: Currently, several types of plasma discharge devices have become established for performing surgical procedures or superficial sterilization. Our goal is to introduce a brand new type of plasma discharge device with different characteristics, which we have used for two experiments involving thermal damage to biological tissues. MATERIAL AND METHODS: A plasma discharge device with the following characteristics was used for all incisions in plasma group: radio frequency barrier discharger at atmospheric pressure with a working frequency of 13.56 MHz. The working gas was Argon. We used a Cesar 136 generator with typical power 100-150W and with a working gas flow rate between 0.5 and 3 litres per minute. The inner diameter of the end of the nozzle was 0.4mm. A standard Martin electrotome was used for all comparative incisions in the electrotome group. We used two experimental fresh rat cadavers, employing their skin, tails, lungs, livers, kidneys and spleens to make a comparative study between incisions made with a plasma discharge knife and those made with a standard electrotome device. All samples underwent histological verification. DISCUSSION: Our experiment showed slight differences in the impact on incision edges made by the plasma knife and the electrotome. The most interesting effect is on the skin: the plasma knife does not damage hair bulbs, and it results in less thermal damage. The plasma discharge knife is a promising device for cutting various biological tissues. Its effect can be compared with a standard electrotome, while in some tissues it causes less harm then an electrotome. Moreover, we can adjust its therapeutic effect. However, we do not consider the plasma knife a better choice at present, because maneuvering it is unwieldy.
Keywords: Liver; Pilot Projects; Rats; játra; kůže; zvířata; plíce; argonová plazmakoagulace; Argon Plasma Coagulation; Kidney; Spleen; Skin; Lung; pilotní projekty; krysa rodu Rattus; ledviny; slezina; Animals